RECOMMENDATIONS FOR TECHNOLOGISTS PERFORM A REPAIR PATH FOR LONG-CLOSED DRIVING AND FINDING TRAIN SPEED AFTER THE COMPLETION OF THESE WORKS - Umanov, M. I.; Tsyhanenko, V. V.; Reidermeister, O. H.; Khalipova, N. V. (Science and Transport Progress, 2007)
In clause offers on technology of performance of modernization of a way are formulated on is long the closed site. On the basis of the analysis of results theoretical and experimental researches recommendations on an establishment of admitted speeds of movement of trains in curves after performance of modernization are formulated on is long the closed site.